Viabilidad de Proyectos de Electrificación Fotovoltaica con Minirredes en la Zona Rural de la Región Áncash - Figueroa Cruz, Myriam (2022)
In our Region there are a large number of small rural communities, this constitutes a great potential for the use of photovoltaic energy through mini-grids for its electrification, this technology suggests an appreciable reduction in installation, operation and maintenance costs. It is important to make the necessary calculations of consumption that allows to cover the basic demand, this implies a greater incidence in the analysis of the social factors that lead to the success of the electrification projects with this technology.